2017
DOI: 10.1016/j.visres.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Action recognition is viewpoint-dependent in the visual periphery

Abstract: Recognizing actions of others across the whole visual field is required for social interactions. In a previous study, we have shown that recognition is very good even when life-size avatars who were facing the observer carried out actions (e.g. waving) and were presented very far away from the fovea (Fademrecht, Bülthoff, & de la Rosa, 2016). We explored the possibility whether this remarkable performance was owed to life-size avatars facing the observer, which - according to some social cognitive theories (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This measure, averaged across all crowd members, represents the amount of motion visible in the image plane calculated across two movie frames. We have shown previously that this measure of motion correlates with the 2D motion energy of the stimuli ( Fademrecht et al., 2017 ). The analysis shows that the amount of movement is indeed significantly higher in the active crowd than in the idle crowd, t (100.59) = 13.91, p < .001, across the movie frames.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This measure, averaged across all crowd members, represents the amount of motion visible in the image plane calculated across two movie frames. We have shown previously that this measure of motion correlates with the 2D motion energy of the stimuli ( Fademrecht et al., 2017 ). The analysis shows that the amount of movement is indeed significantly higher in the active crowd than in the idle crowd, t (100.59) = 13.91, p < .001, across the movie frames.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, action recognition performance in the visual periphery as probed by life-size human stick figures (see example in Figure 3 ) is different from action recognition performance probed by small point-light humans. For example, we have previously shown that action recognition of life-size stick figures (∼32° visual angle [VA]) is excellent up to 75° eccentricity ( Fademrecht, Bülthoff, & de la Rosa, 2016 , 2017 ). In contrast, the detection and discrimination of small point-light walkers (11° VA) was significantly decreased already at 12° eccentricities ( Ikeda, Blake, & Watanabe, 2005 ; Ikeda, Watanabe, & Cavanagh, 2013 ; Thompson, Hansen, Hess, & Troje, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by analysis one may find that in some actions such as drinking, the recognition of interactive region between human and the cup can also provide help for action identification. Since the two-dimensional RGB image is the projection of three-dimensional objects [9], interaction detection in the traditional color images cannot effectively reflect the spatial relationship between human and the object, which will result in error extraction [13][14]. At this point, the depth image has a significant advantage [15].…”
Section: Introductionmentioning
confidence: 99%
“…different actions captured from one same person. These difficult issues constraint the further progress of vide technology based on RGB sequences [6], [7]. However, the release of Kinect sensor presents a new idea and more information to resolve these problems [8]- [10].…”
Section: Introductionmentioning
confidence: 99%